Comparative Study of the Flypaper Effect on Local Government Expenditure in Districts/Cities across Provinces in Java Island - Wulan Setyaningsih; Banu Witono (Yayasan Riset dan Pengembangan Intelektual, 2023)
The aim of this study is to analyze the Flypaper Effect phenomenon on Local Government Expenditure in districts/cities within provinces on Java Island from 2015 to 2022. This research employs secondary data from the population of each province in Java Island, excluding DKI Jakarta due to its non-receipt of General Allocation Fund, with data on DAU, PAD, and Local Government Expenditure. Purposive sampling technique is utilized alongside multiple linear regression analysis. The findings reveal that both the variables of Local Own-Source Revenue (PAD) and General Allocation Fund (DAU) significantly influence Local Government Expenditure in the provinces of Banten, Central Java, East Java, West Java, and DI Yogyakarta. The Flypaper Effect phenomenon is observed in Banten, East Java, West Java, and DI Yogyakarta for the current year, as well as for the previous year's (DAUt-1 and PADt-1) data in Banten, Central Java, East Java, and West Java. However, Central Java does not experience the Flypaper Effect phenomenon for the current year.